Implementasi Elektronik Analisis Beban Kerja (E-ABK) pada Kinerja Pegawai di UPTD Liponsos Dinas Sosial Kota Surabaya - Fajar Harianto, Saefudin; Arundinasari, Indira (IAI Nasional Laa Roiba Bogor, 2024)
This study explores the implementation of the Workload Analysis electronic application (E-ABK) at UPTD Liponsos, under the Social Services Department of Surabaya City, aimed at improving the accuracy of workload assessments and task distribution among employees. Employing a qualitative research approach with a case study design, data were collected through in-depth interviews, direct observations, and document analysis. The findings highlight significant challenges such as resistance to change, technical and infrastructure constraints, human resource readiness, system integration issues, and data management concerns. To address these challenges, strategies including intensive training, infrastructure enhancement, effective communication, and robust data security policies are recommended. The study concludes that with committed management and strategic approaches, E-ABK can enhance employee performance, efficiency, and public service quality.